SHAM TRANSACTIONS AS TRANSACTIONS WITH FLAW IN THE WILL - V. M. Platonov (Russian Journal of Economics and Law, 2014)
Objective: to prove that sham transactions should be considered invalid transactions with flaw in the will. Methods: General scientific method of systemic analysis, making it possible to identify the legal nature of sham transactions and to define its place both in the general system of legal facts, and in the system of invalid transactions. Results: the conclusion is justified that sham transactions should be considered invalid transactions with flaw in the will, because when making a sham transaction the parties have both the will and the declaration of the will, but the declaration of the will does not reflect in full the relations and the consequences that the parties intend to generate. Scientific novelty: the author has reviewed the scientific studies of those who attribute sham transactions to the group of invalid deals with the flaw in the content. Basing of the presented analysis, the author gives counter-arguments, which allow to identify the flaw of sham transactions. Taking into account that only legitimate actions are considered to be transactions, it is proposed to change the wording of Article 153 of the Russian Civil Code. Practical value: the theoretical principles formulated in the study can be used in lawmaking, in teaching courses in Civil Law, as well as other special courses.